Facilely fabricating superhydrophobic coated-mesh materials for effective oil-water separation: Effect of mesh size towards various organic liquids. (15th August 2020) - Chen, Haifeng; Shen, Yizhou; He, Zhaoru; Wu, Zhengwei; Xie, Xinyu
Abstract: Effective oil-water separation is a continuous pursuit, not only for scientific research but also for engineering application, because oil spills are causing the great pollution in the current ocean environment. Here we reported a superhydrophobic coated-mesh, where the coatings were composed of fluorinated silica (F-SiO2 ) and polydimethylsiloxane (PDMS), demonstrating the excellent oil-water separation ability towards various organic liquids. The introduction of F-SiO2 could well induce a certain extent of microscopic roughness, leading to the remarkable water repellence. The resultant coatings exhibited the robust superhydrophobicity with the water contact angle reaching 155.9°±1.0°. On this basis, the pore size of polyethylene terephthalate (PET) mesh materials (as a substrate) was mainly discussed with the great oil-water separation efficiency of as high as 98% towards various organic liquids. Also, under the assistance of physical model, it was confirmed that there was a mechanical relation between pore size and organic liquids, where the main connotation was the matching issue of surface tension of organic liquids with the geometrical mechanic (induced by the pore size of the superhydrophobic coated-mesh). This work on the size effect of superhydrophobic coated-mesh materials on various organic liquids is beneficial to the design and manufacture of ideal oil-water separation materials.